2015
DOI: 10.1128/aem.02601-15
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metagenomic Sequencing to Food Safety: Detection of Shiga Toxin-Producing Escherichia coli on Fresh Bagged Spinach

Abstract: Culture-independent diagnostics reduce the reliance on traditional (and slower) culture-based methodologies. Here we capitalize on advances in next-generation sequencing (NGS) to apply this approach to food pathogen detection utilizing NGS as an analytical tool. In this study, spiking spinach with Shiga toxin-producing Escherichia coli (STEC) following an established FDA culture-based protocol was used in conjunction with shotgun metagenomic sequencing to determine the limits of detection, sensitivity, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 22 publications
2
110
0
3
Order By: Relevance
“…We validated the accuracy of each approach by processing spinach metagenome data from samples that had been spiked with the STEC O157:H7 Sakai in a previous study (11). We observed that PanPhlAn was the most sensitive approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We validated the accuracy of each approach by processing spinach metagenome data from samples that had been spiked with the STEC O157:H7 Sakai in a previous study (11). We observed that PanPhlAn was the most sensitive approach.…”
Section: Discussionmentioning
confidence: 99%
“…Application of strain-level analysis to characterize enteric bacteria in nunu. Leonard et al previously used metagenomic sequencing to detect E. coli in spinach that had been intentionally spiked with E. coli O157:H7 strain Sakai (11). We downloaded the metagenomic reads from that study (16 samples), and we subjected them to StrainPhlAn, MetaMLST, and PanPhlAn analysis to confirm that these tools can accurately detect pathogens in food samples; MetaMLST was used for multilocus sequence typing, StrainPhlAn was used for phylogenetic identification, and PanPhlAn was used for functional characterization.…”
Section: Strain-level Metagenomic Analysis Of Nunumentioning
confidence: 99%
See 1 more Smart Citation
“…It can be used to directly analyze the microorganisms within a sample by sequencing all the genomes in the sample and comparing the genomic data to those of known microorganisms [70][71][72][73][74][75]. In addition to identify the bacteria present in the sample, this method can also be used to analyze the genetic relationship among the organisms assessed, identify putative virulence factors and explore new or rare pathogens.…”
Section: Metagenomicsmentioning
confidence: 99%
“…A relevant application based this metagenomic approach concerns the detection of foodborne pathogens [41,42]. Other metagenomics applications in food safety include the identification of novel and nonculturable agents that cause disease [43].…”
Section: Food Safetymentioning
confidence: 99%